Public goods, international trade, and tax competition - Andreas Haufler (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1992)
The paper sets up an analytical framework within which the arguments for centralized vs. decentralized tax policy can be represented and weighed against each other. Two aspects of the debate are considered: first, the global welfare effects of 'harmonizing' tax reforms are discussed when preferences for public goods differ across countries and non-distorting taxes are not available. Second, the welfare implications of tax competition and tax harmonization are evaluated in a setting where both fiscal and political externalities (Leviathantype governments) exist.
Keywords: 330; Steuerpolitik; Steuerwettbewerb; Öffentliche Güter; Außensteuerrecht; Theorie